Asia's Rising Research Dominance - Benner, Mats (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. Providing an in-depth and cutting-edge investigation into the rise of Asian research practices and paradigms, Mats Benner examines how this rise has been accomplished, what effects it has had, and how it has shaped universities across seven Asian countries.